2013
DOI: 10.15218/zjms.2013.0035
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chest x-ray and clinical finding in children with pneumonia

Abstract: Background and objective:The objectives of the study research were to determine the relationship between clinical and chest X-ray findings of pediatric patients. Methods: A Prospective clinical study carried out at Raparin hospital in Erbil city, Iraq. A sample of 356 children admitted between Decembers 2004 and June 2005 from emergency ward and inwards in Raparin hospital were collected with age range from 2 months to 10 years with mean age of 19 months. All children had chest radiography on the bases of clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
(14 reference statements)
0
5
0
1
Order By: Relevance
“…The commonest auscultator finding is predominantly wheeze and crepitation ( 30% ) which is comparable to Salwa Ahmad Al-Najjar et al study (82%); followed by no finding seen in 19% cases, only wheeze 18% cases, only crepitation in 10% cases, predominantly crepitation with wheeze in 9% cases, diminished Vesicular breath sound (VBS) in 9% cases, Predominantly Bronchial breath sound (BBS) with crepitation and wheeze in 3% cases, diminished Vesicular breath sound with wheeze in 2% cases were present. In my study, Auscultatory chest findings were present bilaterally in 49% cases, in right lung 23% cases, in left lung 11% cases [4].…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…The commonest auscultator finding is predominantly wheeze and crepitation ( 30% ) which is comparable to Salwa Ahmad Al-Najjar et al study (82%); followed by no finding seen in 19% cases, only wheeze 18% cases, only crepitation in 10% cases, predominantly crepitation with wheeze in 9% cases, diminished Vesicular breath sound (VBS) in 9% cases, Predominantly Bronchial breath sound (BBS) with crepitation and wheeze in 3% cases, diminished Vesicular breath sound with wheeze in 2% cases were present. In my study, Auscultatory chest findings were present bilaterally in 49% cases, in right lung 23% cases, in left lung 11% cases [4].…”
Section: Discussionmentioning
confidence: 47%
“…This study also consistent with Brazilian study which showed pulmonary infiltrate and consolidation in 161 cases (54%) and 119(40%) respectively. In this study Interstitial pneumonia was seen in 15 cases (5%) but Salwa Ahmad Al-Najjar et al study showed that it is as common as that of consolidation [4][5][6].…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations